Spin-orbit torque (SOT) effective fields and SOT-induced switching in perpendicularly magnetized multilayers - Li, Sihua (2019)
Spin-orbit torque (SOT) is an electrical-driven phenomenon in which the magnetization of a ferromagnetic material can be switched by the momentum transfer of the diffused accumulated spins at the heavy metal (HM)/ferromagnet (FM) interface, when applying an electric current through the HM layer. The SOT effect is highly attractive from application viewpoint, specifically for faster magnetization switching and lower power non-volatile memory devices. However, the search for in-depth physics understanding of the SOT continues, specifically on the SOT-induced magnetization switching phenomenon. In this thesis, systematic investigation of the physics governing the SOT-induced magnetization switching has been carried out by examining the SOT effective fields, i.e., damping-like term and field-like term. AC harmonic Hall voltage measurement technique was applied to characterize the SOT effective fields in Pt/Co/Ta structure with perpendicular magnetic anisotropy (PMA). It is found that the sign and magnitude of the damping-like term are dependent on the thickness of the inserted Pt layer at the Co/Ta interface, while that is negligible for the field-like term. In the Pt/Co/Pt/Co/Ta structure, the effective field strength is dependent on the lower Co layer thickness while no changes were observed with varying upper Co layer thickness. The asymmetric dependence of the SOT on the two Co layer thicknesses is attributed to the modulations of the saturation magnetization as a result of their different interface conditions. Additionally, by exploiting the intrinsic tilt of the magnetization in the Pt/[Co/Ni]2/Co/Ta structure, it is shown that field-free SOT-induced magnetization switching is possible. Kerr imaging reveals that the field-free SOT switching process is completed via the nucleation of reverse domain and propagation of domain wall in the system.